The Impact of Cooling Water Way Length on Thermal Effluent Temperature Reduction in Coal-fired Steam Power Plants: The Case Study of the 2×150 MW Jeneponto Power Plant - Saiby, Andi Muhammad Subhan; Mustamin, Muhammad Rifaldi; Darwis, Istiawati; Tuwo, Mustamin (Engineering, Technology & Applied Science Research, 2025)
The thermal pollution caused by the usage of fossil energy sources has a significant impact on aquatic ecosystems that requires effective cooling systems for the reduction of temperatures such as the Cooling Water Way (CWW). This study examines the correlation between CWW length and temperature reduction at the Jeneponto power plant (2×150 MW) in Indonesia, focusing on two sections: box culvert (0-359 m) and open channel (359 m-1068 m). The box culvert segment, with minimal air-water interaction, achieves a temperature reduction gradient of 0.0006 °C/m, while the open channel segment shows a higher gradient of 0.0022 °C/m due to the enhanced cooling by convection, evaporation, and radiation. Linear regression models for both segments (R² is 0.9586 and 0.9961, respectively) highlight the important role of channel configuration in cooling efficiency. These findings provide valuable insights for optimizing CWW designs for effective thermal pollution control in coal-fired power plants worldwide.